Antibacterial antibody responses associated with the development of asthma in house dust mite-sensitised and non-sensitised children. Issue 4 (21st November 2011) - Hales, Belinda J; Chai, Lee Ying; Elliot, Claire E; Pearce, Leigh J; Zhang, Guicheng; Heinrich, Tatjana K; Smith, Wendy-Anne; Kusel, Merci M; Holt, Patrick G; Sly, Peter D; Thomas, Wayne R
Abstract : Background: Infants who develop house dust mite (HDM) allergy and HDM-sensitised children with severe persistent asthma have low antibody responses to the P6 antigen of Haemophilus influenzae . Objective: To measure the development of antibody to two ubiquitous bacteria of the respiratory mucosa in a prospective birth cohort at high risk of allergic disease and to assess which responses are associated with asthma and atopy. Methods: IgG1 and IgG4 antibody to H influenzae (P4 and P6) and Streptoccocus pneumoniae (PspA and PspC) surface antigens was measured in yearly blood samples of children aged 1–5 years. IgE to the P6 antigen was examined for the 5-year group. The children were stratified based on HDM sensitisation and asthma at 5 years of age. Results: HDM-sensitised children had lower IgG1 antibody titres to the bacterial antigens, and early responses (<3 years and before the development of HDM sensitisation and asthma) corrected for multiple antigens were significantly reduced for P4, P6 and PspC (p=0.008, p=0.004 and p=0.028, respectively). Similar associations with asthma were also found (p=0.008, p=0.004 and p=0.032 for P4, P6 and PspC, respectively). The IgG4 antibody titre and prevalence were similar in both HDM-sensitised and non-sensitised groups, but sensitised children had a slower downregulation of the IgG4 response. Children with asthma (27/145 at 5 years) had lower anti-P6 IgE responses (p<0.05). Conclusions: HDM-sensitised children have early defective antibody responses to bacteria that are associated with asthma. Surprisingly, antibacterial IgE was associated with a reduced risk for asthma.